Comparative study on encryption algorithms in cloud environment - Suhaimi, Asiah Mastura (2017)
Cloud computing is the Internet based development and used in computer technology where end users are provided with on demand shared resources, software and information. Security is being a major issue in the cloud computing, and it arise attention for Cloud Service Providers (CSP) and end users. Cloud computing security problem raises suspicions and makes many organizations refuse the idea of using the cloud in storing certain data within the cloud computing, especially data with high confidentiality. In addition, cloud users try to avoid being controlled by the CSPs. To avoid the data and data transmission from attackers, appropriate key management is necessary. Besides that, all the data is virtual and cloud is an open service and using a public network such as the Internet for application and services, which has security issues like authentication data loss. Encryption algorithm is a technique that is used to make data on the cloud secured. The aim of the study is to propose the authentication model using Kerberos technique for cloud environment to provides more security. This model can benefit by filtering the unauthorized access and also to reduce the memory usage of cloud provider against authentication checks for each user. It also acts as the third party between cloud server and users to allow authorized access to the cloud services. In this research, the performance of the algorithm is measured based on the computational and communication time. The performance is compared with three algorithms which are RSA, DSA and AES. Result experiment shows that RSA is performing much better than DSA and AES in terms of computational time.